Spatiotemporal Dynamics of Maize (Zea mays L.) Root Growth and Its Potential Consequences for the Assembly of the Rhizosphere Microbiota - Bonkowski, Michael; Tarkka, Mika; Razavi, Bahar S.; Schmidt, Hannes; Blagodatskaya, Evgenia; Koller, Robert; Yu, Peng; Knief, Claudia; Hochholdinger, Frank; Vetterlein, Doris (Frontiers in Microbiology, 2021)
Numerous studies have shown that plants selectively recruit microbes from the soil to establish a complex, yet stable and quite predictable microbial community on their roots – their 'microbiome'. Microbiome assembly is considered as a key process in the self-organization of root systems. A fundamental question for understanding plant-microbe relationships is where a predictable microbiome is formed along the root axis and through which microbial dynamics the stable formation of a microbiome is challenged. Using maize as a model species for which numerous data on dynamic root traits are available, this mini-review aims to give an integrative overview on the dynamic nature of root growth and its consequences for microbiome assembly based on theoretical considerations from microbial community ecology.